Microcarriers with Complex Architectures Manufactured by Two-Photon Lithography for Mechanobiological Manipulation and Expansion of Mesenchymal Stem Cells - Hutchinson, Jason (2023)
Mesenchymal stem cells (MSCs) are a powerful tool in regenerative medicine owing to their innate capacity to differentiate into a range of cell lineages and this behaviour has been utilised as a means of tissue repair and regeneration. The prevalent issue in many treatments is the vast number of cells required for therapeutic effect, but this can be addressed through expansion of cell populations in vitro to suitable levels. Microcarriers are designed to provide a high level of cell growth surface within a small volume and have become one of the most promising expansion tools to date. However, transition to approaches that integrate biomechanical cues to modulate cell responses can lead to far greater outcomes than those that can be achieved through surface area alone. Such biophysical properties that can be integrated include geometry, roughness, topography, stiffness, and porosity which can promote specific biological responses through mechanotransduction pathways. This thesis focuses on employing this approach to microcarrier technology and examining the effects of such structures on cell control and enhancement of expansion yield to facilitate MSC production for therapeutic uses. Two-photon lithography was employed to produce microcarriers with highly complex geometry at sub-micron feature size and optimisations allowed fabrication speed to be increased by up to 423-fold at the cost of structure resolution. Biocompatibility testing identified several suitable acrylate polymers with varying characteristics but highlighted the need for further materials exploration due to suboptimal adherence in most candidates. Novel fabrication techniques allowed cell culture isolation to structures without complication by anchoring substrates which addressed a continuing issue with two-photon derived samples that has been presented in the literature. A variety of produced designs exhibited significant increase in cell proliferation and consistent interaction with structure features with observable cellular preference for certain feature types and sizes. From these selected designs further morphological analysis of cells and DNA quantification determined microcarrier designs that lead to a significant increase in expansion yield in comparison to a conventional microcarrier design. Best expansion yields were seen in Buckminsterfullerene styled structures with hollow interiors and porous outer shells and identified that expansion yield was not necessarily based on the amount of surface area alone. Analysis of stem cell phenotype changes across expansion periods indicated mixed results in the maintenance of phenotypes and requires further exploration. This thesis demonstrated biomechanical based enhancement of expansion proficiency as well as novel techniques relating to two-photon lithography. However, for scale up of work and translation to clinical applications a significant increase in microcarrier production is necessary. Microcarriers that intelligently shape cellular proliferation and differentiation present an opportunity to act both in vitro and in vivo evolving beyond their primary function of expansion and acting as multifunctional tissue modulators.